2005
DOI: 10.1557/jmr.2005.0317
|View full text |Cite
|
Sign up to set email alerts
|

Constraint Effects on Thin Film Channel Cracking Behavior

Abstract: -One of the most common forms of cohesive failure observed in brittle thin film subjected to a tensile residual stress is channel cracking, a fracture mode in which through-film cracks propagate in the film. The crack growth rate depends on intrinsic film properties, residual stress, the presence of reactive species in the environments, and the precise film stack. In this paper, we investigate the effect of various buffer layers sandwiched between a brittle carbon-doped-silicate (CDS) film and a silicon substr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
50
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(51 citation statements)
references
References 11 publications
1
50
0
Order By: Relevance
“…While some experimental observations clearly showed channel cracks with no delamination [16,19], others observed delamination of the interface [16,20] (Fig. 1b).…”
Section: Interfacial Delamination From Channelmentioning
confidence: 96%
See 3 more Smart Citations
“…While some experimental observations clearly showed channel cracks with no delamination [16,19], others observed delamination of the interface [16,20] (Fig. 1b).…”
Section: Interfacial Delamination From Channelmentioning
confidence: 96%
“…The effect of constraint can be partly lost as the substrate deforms plastically [13] or viscoelastically [14,15]. More recent studies have investigated the effects of stacked buffer layers [16,17] and patterned film structures [6]. In most of these studies, the interfaces between [11,12].…”
Section: Channel Crackingmentioning
confidence: 99%
See 2 more Smart Citations
“…1). Previous studies have shown that the driving force for the steady state growth of a channel crack (i.e., energy release rate) depends on the constraint effect of surrounding layers [1,4]. For a brittle thin film on an elastic substrate, the driving force increases for increasingly compliant substrates [5,6].…”
Section: Introductionmentioning
confidence: 99%